(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
In this paper, a thick disk with aspect ratio greater than 1/10 is directly simulated by adaptive mesh refinement-immersed boundary-lattice Boltzmann flux solver (AMR-IB-LBFS). The AMR-IB-LBFS model is a combination of the adaptive mesh refinement (AMR) technique and immersed boundary-lattice Boltzmann flux solver (IB-LBFS). Four different aspect ratio disks are numerically simulated, and the numerical results are in good agreements with theoretical results. In addition, these disks with different aspect ratios are compared with trajectories and gestures.